Colonization nation an experiential memorial landscape in Mt. Tagapo, Rizal Province, to the Filipino hardship during the three colonial periods - Atienza, Marian S.
Colonialism in the Philippines is deeply rooted and pervasive at present. Philippine society is riddled with colonial mentality, cultural confusion, susceptibility to foreign oppression, and indefference for own heritage. These are signs that the nation is under a new era called 'Neo-Coloonialism'. There is also the perspective that most of the nation's social issues can be traced back to colonialism, such as racism, corruption, elitism, etc. These issues occur and often repressed by modern Filipino which hinder the actualization of the nation. This study, "Colonization Nation", aims to seek experential methods in historical memorialization to combat the repressive Filipino attitude that is present towards the topic of colonization in the Philippines. The resulting landscape design showcases seven (7) Filipino Hardships during colonial times, namely: racism, corruption, elitism, fascism, misogyny, deception, and chauvanism. These Filipino Hardships in the form of 'nodes' in the memorial landscape carries out an experiential quality so that the users, Modern Filipinos, may form empathy towards the experience of Past Filipinos.